Hadith #5385 - Sahih al-Bukhari - Abu Al-Juwairiyya (Sahih al-Bukhari)
I asked Ibn `Abbas about Al-Badhaq. He said, “Muhammad prohibited alcoholic drinks before It was called Al-Badhaq (by saying), ‘Any drink that intoxicates is unlawful.’ I said, ‘What about good lawful drinks?’ He said,’Apart from what is lawful and good, all other things are unlawful and not good (unclean Al-Khabith).
Grade: Sahih